Determinants of personal financial planning an empirical investigation / Khairina Izwani Mohd Idris and Nur Aziana Farahin Sahid - Mohd Idris, Khairina Izwani; Sahid, Nur Aziana Farahin (Faculty of Business and Management, 2014)
Awareness towards personal financial planning has been viewed as an important thing which can determine the financial position among public in Shah Alam. This study therefore explore the factors influencing the personal financial planning and to study the relationship of financial literacy, employee consciousness, impulsive spending behaviour and stress towards awareness on personal financial planning.We discover that financial literacy, employee consciousness, impulsive spending behaviour and stress are instrumental in determining one’s awareness towards personal financial planning. In more details, employee consciousness is firstly ranked, followed by financial literacy which comes second. Those factor identified provide better information and valuable insights to direct future awareness on personal financial planning.